Learning to love you more - Fletcher, Harrell; July, Miranda (Munich ; London : Prestel, 2007)
In a world obsessed with 'reality' programming, the collaborative public art project known as "Learning To Love You More" offers a take on how people think, act and love. The web-based project, begun in 2002, offers more than sixty 'assignments' that can be completed by anyone. This book presents a selection of the most memorable submissions.
boek
Keywords: Art and society; Community arts projects